Ionospheric Feedback and ULF Quarter‐Waves. Issue 9 (16th September 2022) - Streltsov, Anatoly V.; Mishin, Evgeny V.
Abstract: This paper presents results from the numerical investigation of nonlinear feedback interactions between ULF field‐aligned currents (FACs) and the ionospheric plasma in the global magnetospheric resonator with a non‐symmetrical distribution of the plasma density in the conjugate hemispheres. The density asymmetry is enhanced by the introduction of the ionospheric valley in the hemisphere where the plasma density is already lower. The main result from this study is that in the non‐symmetrical resonator, the ionospheric feedback mechanism, driven by the electric field with the maximum amplitude of 50 mV/m, develops nonlinear, intense, small‐scale upward currents with a characteristic quarter‐wavelength structure along the ambient magnetic field. The frequency of these waves is two times less than the fundamental frequency of the symmetrical resonator. The ionospheric valleys, which are depletions of the plasma density between the ionospheric E and F regions, enhance this effect, by reducing the effective ionospheric conductivity. This effect is important for the interpretation of ground, satellite, and sounding rocket observations of ULF waves and FACs in the auroral and subauroral geospace. Key Points: We model nonlinear feedback interactions between ULF field‐aligned currents and the ionospheric plasma Simulations show that these interactions produce ULF quarter‐waves in the global resonator with a non‐symmetric density distribution Ionospheric valley enhances this effect by decreasing the effective conductivity of the ionosphere